Pembelajaran Embedded System Berbasis Arduino Mega 2560 dan MIT App Inventor (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
This paper describes the learning process of the Embedded System course with a practical approach based on Arduino Mega 2560 and Android using MIT App inventor software. Learning materials include digital I / O and analog I / O access via android mobile phone. The method used in its implementation premises to provide tasks in the form of projects. The next step is to find the theories that can support in completing the project task. The project task is to control or read electronic devices connected via digital I / O or analog I / O. The most basic project is to control an on-off LED connected to an arduino digital output pin and read the digital input signal generated from a switch connected to an arduino pin via a mobile phone. Delivery from arduino to mobile phone or mobile phone to arduino via bluetooth.